tìm x
a)\(\frac{12}{x}+9=45\)
a)\(5x+8-4x=72\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\Rightarrow72-20x-36x+84=30x-240-6x-84\)
\(\Rightarrow80x=480\Rightarrow x=6\)
b) \(\Rightarrow15x+25-8x+12=5x+6x+36+1\)
\(\Rightarrow4x=0\Rightarrow x=0\)
c) \(\Rightarrow10x-16-12x+15=12x-16+11\)
\(\Rightarrow14x=4\Rightarrow x=\dfrac{2}{7}\)
ĐKXĐ: \(x\ne\pm\frac{3}{2}\)
\(\frac{1}{\left(2x-3\right)^2}+\frac{3}{\left(2x-3\right)\left(2x+3\right)}-\frac{4}{\left(2x+3\right)^2}=0\)
\(\Leftrightarrow\frac{1}{\left(2x-3\right)^2}-\frac{1}{\left(2x-3\right)\left(2x+3\right)}+\frac{4}{\left(2x-3\right)\left(2x+3\right)}-\frac{4}{\left(2x-3\right)^2}=0\)
\(\Leftrightarrow\frac{1}{2x-3}\left(\frac{1}{2x-3}-\frac{1}{2x+3}\right)-\frac{4}{2x-3}\left(\frac{1}{2x-3}-\frac{1}{2x+3}\right)=0\)
\(\Leftrightarrow\left(\frac{1}{2x-3}-\frac{4}{2x+3}\right)\left(\frac{1}{2x-3}-\frac{1}{2x+3}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}2x+3=2x-3\left(vn\right)\\2x+3=4\left(2x-3\right)\Rightarrow x=\frac{5}{2}\end{matrix}\right.\)
`a)sqrt{5x-2}=3(x>=2/5)`
`<=>5x-2=9`
`<=>5x=11`
`<=>x=11/5(tm)`
`b)sqrt{x^2-4x+4}-5=0`
`<=>\sqrt{(x-2)^2}=5`
`<=>|x-2|=5`
`<=>` \(\left[ \begin{array}{l}x-2=5\\x-2=-5\end{array} \right.\)
`<=>` \(\left[ \begin{array}{l}x=7\\x=-3\end{array} \right.\)
`c)3sqrt{4x+8}-sqrt{9x+18}+9sqrt{(x+2)/9}=sqrt{72}(x>=-2)`
`<=>6sqrt{x+2}-3sqrt{x+2}+3sqrt{x+2}=sqrt{72}`
`<=>6sqrt{x+2}=6sqrt2`
`<=>sqrt{x+2}=sqrt2`
`<=>x+2=2`
`<=>x=0(tm)`
\(a,ĐK:x\ge\dfrac{2}{5}\)
\(\Leftrightarrow5x-2=9\)
\(\Leftrightarrow5x=11\)
\(\Leftrightarrow x=\dfrac{11}{5}\)
\(b,\)
\(\Leftrightarrow x^2-5x+4=25\)
\(\Leftrightarrow x^2-5x-21=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5+\sqrt{109}}{2}\\x=\dfrac{5-\sqrt{109}}{2}\end{matrix}\right.\)
\(c,\)
\(\Leftrightarrow6\sqrt{x+2}-3\sqrt{x+2}+9\cdot\sqrt{\dfrac{x+2}{9}}=6\sqrt{2}\)
\(\Leftrightarrow2\sqrt{x+2}-\sqrt{x+2}+3\cdot\sqrt{\dfrac{x+2}{9}}=2\sqrt{2}\)
Đặt \(\sqrt{x+2}=a\) ta có (1)
\(2a-a+3\cdot\dfrac{a}{\sqrt{9}}=2\sqrt{2}\)
\(\Leftrightarrow a+3\cdot\dfrac{a}{3}=2\sqrt{2}\)
\(\Leftrightarrow2a=2\sqrt{2}\)
\(\Leftrightarrow a=\sqrt{2}\)
Thay \(a=\sqrt{2}\) vào (1) ta có
\(\sqrt{x+2}=\sqrt{2}\)
\(\Leftrightarrow x+2=2\)
\(\Leftrightarrow x=0\)
a) \(\sqrt{1-4x+4x^2}=5\)
<=> \(\sqrt{4x^2-4x+1}=5\)
<=> 4x2 - 4x + 1 = 52
<=> 4x2 - 4x + 1 = 25
<=> 4x2 - 4x + 1 - 25 = 0
<=> 4x2 - 4x - 24 = 0
<=> 4(x + 2)(x - 3) = 0
<=> x = -2 hoặc x = 3
=> x = -2 hoặc x = 3
b) \(\sqrt{4-5x}=12\)
<=> \(\sqrt{-5x+4}=12\)
<=> -5x + 4 = 122
<=> -5x + 4 = 144
<=> -5x = 144 - 4
<=> -5x = 140
<=> x = -28
=> x = -28
\(a,\sqrt{1-4x+4x^2}=5\)
\(\Rightarrow4x^2-4x+1=25\)
\(\Rightarrow4x^2-4x-24=0\)
\(\Rightarrow x^2-x-6=0\)
\(\Rightarrow x^2-3x+2x-6=0\)
\(\Rightarrow x\left(x-3\right)+2\left(x-3\right)=0\)
\(\Rightarrow\left(x-3\right)\left(x+2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=3\\x=-2\end{cases}}}\)
\(b,\sqrt{4-5x}=12\)
\(\Rightarrow4-5x=144\)
\(\Rightarrow5x=-140\)
\(\Rightarrow x=-28\)
\(\frac{12}{x}\)+ 9 = 45
\(\frac{12}{x}\) = 36
x = \(\frac{12}{36}\)= 1/3
b) 5x + 8- 4x = 72
(5x-4x) +8 = 72
x + 8 = 72
x = 72-8
x= 64
\(a,\frac{12}{x}+9=45\)
\(\Rightarrow\frac{12}{x}=45-9=36\)
\(\Rightarrow x=12:36=\frac{1}{3}\)
\(b,5x+8-4x=72\)
\(\Rightarrow5x-4x=72-8\)
\(\Rightarrow x=64\)